Achieving carbon neutrality in China: Spectral clustering analysis of plant diversity - Li, Ping; Li, Rita Yi Man; Chen, Hong; Cao, Yong; Kaabar, Mohammed K. A. (Frontiers in Environmental Science, 2022)
Plants have a long history and diverse species. They play a critical role in the ecological chain, human production and life. With a vast territory, China has rich plant species and complex geographical regions, and research on the distribution of plant diversity in China is significant for utilising, developing, and protecting biological resources. This study aimed to study plant diversity in China. It obtained the plant diversity distribution data in China, then analysed it via spectral clustering and visualised it via Echarts. It was found that Yunnan records the most considerable plant diversity, followed by Sichuan and Tibet, meaning that the Southwestern part of China has the most extensive plant diversity. While it is expected that Tibet and Yunnan have backward economic development and hence a lower level of human destruction on plant diversity, Sichuan’s economic development is quite good. The land of abundance still has a wide variety of plants owing to excellent irrigation projects since 256BC. Besides, the Hengduan Mountains were the main route for Chinese plants to migrate from the west to the east, which might be closely related to the Himalayan orogeny. The Himalayan orogeny promotes the formation of the Qinghai–Tibet Plateau, which is a vital factor in the biodiversity formation in China. This study provides a basis for China’s conservation and study and enhances our understanding of plant biodiversity. As plant biodiversity increases soil organic carbon storage, it offers insights into carbon neutrality practitioners and researchers.